Physio-chemical effects on the temperature-dependent elasticity of cement paste during setting. (November 2022) - Huang, Tingjie; Yuan, Qiang; Zuo, Shenghao; Yao, Hao; Zhang, Kai; Wang, Yuman; Xie, Youjun; Shi, Caijun
Abstract: This paper elucidated the temperature dependence of cement setting by comparing the storage modulus (Gʹ) evolutions under different temperatures ranging from 10 to 55 °C. The temperature-induced changes in cement hydration and colloidal interaction were also explored to reveal the underlying physio-chemical effects. It was found that the increase in temperature significantly accelerates the growth of Gʹ in all the stages of setting process, which mainly arises from the promotion of forming "calcium silicate hydrates (C–S–H) bridges" and compressing the electrical double layer of particles. For the same hydration degree, the rise of temperature leads to a greater Gʹ of cement paste. It was attributed to the diminution of the electrostatic repulsive force between particles caused by not only the direct effect of rising temperature but also the higher SO4 2- /Ca 2+ concentration ratio of interstitial solution in the paste cured at the higher temperature.